Penerapan Importance Performance Analysis (IPA) Untuk Mengukur Kualitas Indeks Kepuasan Masyarakat (IKM) Layanan Balai Besar Inseminasi Buatan Singosari-Malang - Rini Hermawati (Jurnal Penelitian dan Pendidikan IPS, 2019)
This study aims to (1) know and analyze the quality and service satisfaction on Artificial Insemination (AIC) Singosari based application Importance Performance Analysis (IPA), (2) to determine the quality of people's satisfaction on service Center for Artificial insemination (AIC) Singosari by Community Satisfaction Index (HPI). The study used a descriptive quantitative survey methods. The population is at BBIB Singosari service users. Acidental samples using sampling techniques with the number of respondents 150 people. Mechanical data using questionnaires and interviews. The analysis is IKM, Gap Analysis and IPA. The results showed: (1) Elements of SME value interests quality levels; A conversion 3,946 SMEs; 98.65, very high SME category means satisfactory service. The level of quality performance IKM value; 4.256 conversions; 106.4, category Very important, so the intervals above 100.00 on a performance level of "A" / Very Good. (2) The results of the study of Interest and Performance with priority mapping IPA there are aspects that need to be improved to make it better. That is; realiability, performance conformity -1.1, -0.1 tangibles, empathy suitability -0.4 performance. To obtain follow-priority repairs by BBIB Singosari.